2019
DOI: 10.1111/ajpy.12230
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and psychological wellbeing of racehorse industry workers: A survey of Australian trainers

Abstract: Background and Objectives This study investigated psychological wellbeing and sleep characteristics in Victorian racing industry workers, specifically focusing on trainers. There are few empirical studies of psychological wellbeing in the horse racing industry, despite considerable employment numbers and a potentially complex and challenging work environment. Early morning starts, and potentially long working days could compound negative wellbeing outcomes. Methods A survey assessing psychological wellbeing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Examples of shift workers who typically start work in the pre-dawn period include garbage collectors, bakers, short-haul airline pilots, and some factory workers. In a previous study by our group, we found that racehorse trainers, who also typically start work in the pre-dawn period, reported elevated levels of depression and anxiety ( 8 ). Daytime dysfunction due to poor sleep was found to be a potentially important causative factor in their higher levels of psychological distress.…”
Section: Introductionmentioning
confidence: 85%
“…Examples of shift workers who typically start work in the pre-dawn period include garbage collectors, bakers, short-haul airline pilots, and some factory workers. In a previous study by our group, we found that racehorse trainers, who also typically start work in the pre-dawn period, reported elevated levels of depression and anxiety ( 8 ). Daytime dysfunction due to poor sleep was found to be a potentially important causative factor in their higher levels of psychological distress.…”
Section: Introductionmentioning
confidence: 85%